Conservation, tourism and pastoral livelihoods : wildlife conservancies in the Maasai Mara, Kenya - Bedelian, C. E. (University College London (University of London), 2014)
The pastoral rangelands of the Mara in Kenya have been a hotspot of evolving conservation and development initiatives. However, these initiatives have tended not to produce positive outcomes for either people or wildlife. At the same time, pastoral policies have promoted the privatisation of rangelands, subdividing the land to individual ownership. Within this backdrop, a number of wildlife conservancies have been recently set up where tourism investors pay Maasai landowners to vacate their land of settlements and livestock. As market-driven approaches that have profound impacts on the way land is viewed, used and managed in the Mara, this thesis situates itself within the growing body of literature on neoliberal conservation. The study takes a mixed methods approach to evaluate these initiatives for pastoral livelihoods and the environment. Using a political ecology lens it analyses the nature of the partnership between the tourism investors and Maasai landowners and the levels of participation and power between different actors. It investigates the contribution of wildlife conservancies to pastoral livelihoods, and uses evaluation techniques to assess the impact of participation in conservancies on pastoral livelihoods. It also examines the resultant settlement and livestock grazing displacement and the implications this has for livelihoods and the wider landscape. The thesis finds that conservancies can contribute large incomes from tourism to participating households. However, this is not more than the contribution of livestock, meaning that conservancy land use restrictions create considerable trade-offs for livestock-based livelihoods. Also, since payments are based on land ownership, and a previously inequitable system of land distribution, there are considerable inequity implications of such schemes as poor and marginalised groups tend to be left out. Furthermore, although conservancies are positive in keeping the range open for wildlife inside of conservancies, this must be considered in light of the displacement effects to non-conservancy areas.